2007
DOI: 10.1007/s10750-006-0570-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of Campsurus notatus (Ephemeroptera: Polymitarcytidae) bioturbation and sediment quality on potential gas fluxes in a tropical lake

Abstract: About 30% of the total area of Lake Batata (Amazon) was impacted by the disposal of bauxite tailings originated from the process of washing bauxite. This effluent, composed by fine particles of clay and water, settled on top of the natural sediment, originating a new substratum with a different physical and chemical composition. This phenomenon created a new distinct habitat (impacted sediment) influencing the benthic community. The aim of this study was to evaluate the impact of bioturbation by Campsurus nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
2
13
0
2
Order By: Relevance
“…Different processes may underlie the fish‐induced reduction in ebullition. For one, bioturbation may physically prevent bubbles from building up in the sediment (as suggested by Leal et al., ) through the mixing of pore‐water with more diluted water overlaying the sediment thereby impeding CH 4 concentrations in the pore‐water to reach the saturation concentration and hence prevent bubble formation. For another, bioturbation may impede the formation of bubbles by enhancing CH 4 oxidation or decreasing CH 4 production.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Different processes may underlie the fish‐induced reduction in ebullition. For one, bioturbation may physically prevent bubbles from building up in the sediment (as suggested by Leal et al., ) through the mixing of pore‐water with more diluted water overlaying the sediment thereby impeding CH 4 concentrations in the pore‐water to reach the saturation concentration and hence prevent bubble formation. For another, bioturbation may impede the formation of bubbles by enhancing CH 4 oxidation or decreasing CH 4 production.…”
Section: Discussionsupporting
confidence: 83%
“…Ebullitive fluxes are known to be strongly influenced by warming, often even more so than diffusive fluxes (Aben et al, 2017). Ebullition was not related to temperature in our mesocosms, which may be ex- in the sediment (as suggested by Leal et al, 2007) through the mixing of pore-water with more diluted water overlaying the sediment thereby impeding CH 4 concentrations in the pore-water to reach the saturation concentration and hence prevent bubble formation.…”
Section: Fish Effects On Ch 4 Emissionsmentioning
confidence: 73%
See 1 more Smart Citation
“…The impact of bioturbation by Campsurus notatus (Ephemeroptera: Polymitarcytidae) on potential gas fluxes in the sediment of Lake Batata was studied by Leal et al (2007). who reported that the new substratum of the lake decreased methane concentrations in sediment and water column.…”
Section: Restoration and Treatmentmentioning
confidence: 99%
“…In aquatic ecosystems, bioturbation by benthic invertebrates is a key process altering microbial community structure and geochemical gradients of sediments and regenerating multiple nutrients across the benthic-pelagic interface (Kristensen et al, 2012). Although numerous studies have evaluated the importance of invertebrate bioturbators to the fluxes of inorganic nutrients (mostly N and P) across the sediment-water interface (Emmerson et al, 2001;Leal et al, 2003;Caliman et al, 2011), only a handful studies have tested the effects of invertebrate bioturbators on CH 4 cycling in sediments (see Kajan and Frenzel, 1999;Leal et al, 2007;Figueiredo-Barros et al, 2009) and no study to date has evaluated the effects of bioturbators biodiversity on sediment CH 4 concentration (hereafter [CH 4 ]). This neglect is important for some different reasons.…”
mentioning
confidence: 99%